1995
DOI: 10.1006/qres.1995.1083
|View full text |Cite
|
Sign up to set email alerts
|

Paleorainfall Reconstructions from Pedogenic Magnetic Susceptibility Variations in the Chinese Loess and Paleosols

Abstract: The rock magnetic properties of the Chinese loess and paleosols constitute a unique and sensitive record of East Asian paleoclimate through the Quaternary Period. Systematic variations in the concentration and grain size of the magnetic minerals in these sediments have produced systematic variations in the magnetic susceptibility signal, which can be easily and rapidly measured at many sites across the Loess Plateau. Variations in many other rock magnetic properties can be used to identify the key shifts in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
214
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 411 publications
(226 citation statements)
references
References 20 publications
10
214
1
1
Order By: Relevance
“…However, Fe d may increase more rapidly than Hm/(Hm+Gt) decreases in low-rainfall regions (Figures 6a and 6b), and the content of Hm (or Mgh) as their product can increase (Figure 6c). In this case, we can reconstruct the paleorainfall by the positive correlation between Fe d , MS, and rainfall as shown in previous studies in temperate regions with low and moderate rainfall [Kukla et al, 1988;Liu et al, 1995;Maher and Thomson, 1995;Maher, 1998]. However, with increasing rainfall, Fe d levels off compared to the decrease in Hm/(Hm+Gt) (Figures 6a and 6b), resulting in a decrease in the content of Hm or Mgh (Figure 6c).…”
Section: Model Of Magnetic Change With Climatesupporting
confidence: 63%
See 1 more Smart Citation
“…However, Fe d may increase more rapidly than Hm/(Hm+Gt) decreases in low-rainfall regions (Figures 6a and 6b), and the content of Hm (or Mgh) as their product can increase (Figure 6c). In this case, we can reconstruct the paleorainfall by the positive correlation between Fe d , MS, and rainfall as shown in previous studies in temperate regions with low and moderate rainfall [Kukla et al, 1988;Liu et al, 1995;Maher and Thomson, 1995;Maher, 1998]. However, with increasing rainfall, Fe d levels off compared to the decrease in Hm/(Hm+Gt) (Figures 6a and 6b), resulting in a decrease in the content of Hm or Mgh (Figure 6c).…”
Section: Model Of Magnetic Change With Climatesupporting
confidence: 63%
“…MS has been suggested as a proxy to reconstruct paleorainfall in temperate monsoon zones, especially for the eolian sediments on the Chinese Loess Plateau (CLP) [Kukla et al, 1988;Heller et al, 1993;Liu et al, 1995;Maher and Thomson, 1995;Maher, 1998]. However, a growing body of evidence suggests a negative correlation between ferrimagnets and rainfall in extreme climates with excessive rainfall [Begét et al, 1990;Han et al, 1996;Singer et al, 1996;Chlachula et al, 1998;Liu et al, 2001Liu et al, , 2003Balsam et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The new steppe magnetic data can be incorpo- rated into Maher and Thompson's (1995) Northern Hemisphere temperate zone dataset. As can be seen from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Maher and Thompson (1995) reconstructed paleoprecipitation of CLP in the last glacial and interglacial by the susceptibility of topsoil. In the last interglacial (S1), the MAP is~25% higher than that of today and varied greatly by region.…”
Section: Paleoprecipitation Reconstruction Of L1-s5 From Lc and Smxmentioning
confidence: 99%
“…Magnetic parameters, which are fast, inexpensive, non-destructive, and sensitive, have been commonly used as indicators of paleoprecipitation for decades, especially the mass-specific susceptibility (χ) (Balsam et al, 2004;Balsam et al, 2011;Liu et al, 2007;Liu et al, 2012;Maher, 1998;Maher et al, 2002;Maher and Possolo, 2013;Maher et al, 1994;Orgeira and Compagnucci, 2006). Maher and Thompson (1995) reported that pedogenic χ (defined as χ-χ C , where χ C represents the χ of the parent material) rises to a peak until MAP reaches about to reductive dissolution or alteration of the iron oxides. Han et al (1996) studied magnetic properties of 160 modern silt soil samples in China and found that the susceptibility of these soils is related not only with mean annual precipitation (MAP) but also with mean annual temperature (MAT).…”
Section: Introductionmentioning
confidence: 99%